2006
DOI: 10.1007/s11524-006-9087-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Partner Notification for C. trachomatis and N. gonorrhoeae: An Examination of Social Cognitive and Psychological Factors

Abstract: Efforts to control chlamydial and gonococcal infections include notifying eligible sexual partners of possible infection, primarily by asking the diagnosed patient to notify their partners. This approach, known as patient referral, is widely used but poorly understood. The current study examined psychosocial and cognitive factors associated with patient referral among an urban, minority sample of 168 participants recently diagnosed with Chlamydia trachomatis or Neisseria gonorrhoeae. At a followup interview 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
4
16
1
Order By: Relevance
“…13 One of the challenges in PN for STI is identification and screening of casual sexual partners of patients with STI. 14,15 Similarly, in the present audit, notification of casual partners was not successful. More research on successful methods for notification of casual sexual partners is urgently needed.…”
Section: Discussioncontrasting
confidence: 52%
“…13 One of the challenges in PN for STI is identification and screening of casual sexual partners of patients with STI. 14,15 Similarly, in the present audit, notification of casual partners was not successful. More research on successful methods for notification of casual sexual partners is urgently needed.…”
Section: Discussioncontrasting
confidence: 52%
“…Our PN rate among pregnant teens was similar to non-pregnant teens in other, smaller cohorts. 5 -9 Although other investigators found alcohol consumption influences PN, 24 our pregnant population reported such low rates of Table 5 Comparison of pregnant and non-pregnant women with regard to anticipating future sexual intercourse with male partner(s) and PN alcohol, drug or tobacco use, that the PN analysis was limited by small cell size.…”
Section: Discussionmentioning
confidence: 79%
“…5,8,11,13,16 -19,24,29,31 We, like others, found that index patients who anticipated ongoing sexual activity with exposed partners were more likely to disclose their infection. 5,11,13,18,24,29,31 The recency of sexual intercourse has also been shown to positively influence PN. 13,17,18,29 The Cochrane database reports that the domestic violence implications of PN are important research topics.…”
Section: Discussionmentioning
confidence: 99%
“…Research also suggests that people with high levels of psychological distress tend to use avoidant-oriented coping strategies (for example, substance use or withdrawal) to manage stressful situations (Penedo et al 2003). Few studies to date have explored the impact of psychosocial and behavioral constructs on PN activities (Schwartz et al 2006) and none have focused on predictors of PN use among MSM.…”
Section: Introductionmentioning
confidence: 99%